Strategic Asset Allocation in Money Management - BASAK, SULEYMAN; MAKAROV, DMITRY (Journal of Finance, 2014)
ABSTRACT This paper analyzes the dynamic portfolio choice implications of strategic interaction among money managers who compete for fund flows. We study such interaction between two risk‐averse managers in continuous time, characterizing analytically their unique equilibrium investments. Driven by chasing and contrarian mechanisms when one is well ahead, they gamble in the opposite direction when their performance is close. We also examine multiple and mixed‐strategy equilibria. Equilibrium policy of each manager crucially depends on the opponent's risk attitude. Hence, client investors concerned about how a strategic manager may trade on their behalf should also learn competitors' characteristics.